Enabling Compassionate Health Care: Perils, Prospects and Perspectives - Russell Mannion (Kerman University of Medical Sciences, 2014)
There is an emerging consensus that caring and compassion are under threat in the frenetic environment of modern healthcare. Enabling and sustaining compassionate care requires not only a focus on the needs of the patient, but also on those of the care giver. As such, threats and exhortations to health professionals are likely to have limited and perverse effects and it is to the organisational and system arrangements which support staff that attention should shift. Any approach to supporting compassionate care may work for some services, for some patients and staff, some of the time. No single approach is likely to be a panacea. Unravelling the contexts within which different approaches are effectual will allow for more selective development of support systems and interventions.